BUILDING BUFFALOS: A PRODUCTION ALTERNATIVE IN THE PROVINCE OF GUAYAS, ECUADOR - Leoro Llerena, Mónica Jackeline (2020)
In the scientific article, the main potential of buffalo production was analyzed as a complementary alternative to cattle production in the Salitre Canton of the Guayas province. The study had as background a first stage of preliminary diagnostic study on the raising of buffaloes in 2018. The objective of this article was to analyze the potentialities of water buffalo production (Bubalus bubalis) as a productive alternative that contributes to the improvement of the economic results of the farmers of the Association El Salitre of the canton Salitre of the province of Guayas. In order to achieve this objective, exploratory and descriptive research was used based on the application of the survey, interviews and direct observation that allowed for the raising of buffaloes as an alternative for livestock production based on the projection of some expenses and income from Sale of meat and milk. The investigation allowed us to conclude that livestock production with the gradual introduction of buffalo breeding will contribute to improving the economy of farmers by having a type of cattle for meat and milk of good quality in its composition, resistant to the conditions of the season of rains and diseases without diminishing yields.